Cooperation and distrust in extra-legal networks: a research note on the experimental study of marketplace disruption - Sebagh, Lonie (Global crime, 2022)
Cybercriminal markets serve as hubs for offenders and enable the sale of illegal goods and services. Thus far, the primary tactics that have been employed against these sites are arrests of cybercriminals and takedowns of marketplace infrastructure. This research note examines a different genus of disruptive strategy: attacks on user reputation. In this area, there has been some scholarly discussion of slander and Sybil operations as a means of fostering distrust. But carrying out empirical work on the effectiveness of these tactics is challenging. This research note presents a possible method for investigating this topic: social laboratory experiments. It reports on a feasibility pilot study inspired by cybercrime disruption, but which speaks to a broader range of extra-legal markets.